Decision of Implementing Uzlah and Gerbat Techniques in Islamic Boarding School as Preparedness Response for Covid-19 Pandemic (Unnes Journal of Public Health, 2020)
The purpose of this study is to describe the decision making and implementation of the uzlah and gerbat techniques by the Salafiyah Syafi'iyah Islamic Boarding School from Sukorejo Situbondo as an educational institution supported by 12,247 boarding students, for preventing Covid-19 transmission. This was a qualitative research using ethnography and hermeneutics data analysis. The outcome was to consider the decision to apply the uzlah and gerbat techniques, because both techniques are historical, theological, and follow the government's recommendations in deciding the distribution of Covid-19. While the implementation, among others: 1) uzlah technique: students are expelled from the Islamic boarding school complex and activated by outsiders. 2) gerbat technique, namely the reading of prayers to avoid a plague. In approving the transmission of Covid-19, Islamic boarding schools balance the technique of uzlah and gerbat, harmonize the lahiriyah (visible) and batiniyah (invisible) approaches.